Analysis of Ministry of Health Regulation No. 30 of 2022 on Hospital Service Quality In Indonesia - Arga Setyo Adji (ARRUS Journal of Social Sciences and Humanities, 2024)
Indonesian Ministry of Health Regulation No. 30 of 2022 has become a focal point in efforts to improve the quality of services in hospitals. In this context, this study aims to investigate the extent of the effectiveness of this regulation and the key factors influencing its implementation in the hospital accreditation process. This study examines the effectiveness of this regulation and the key factors affecting the hospital accreditation process. The research used a mixed approach with qualitative and quantitative techniques and analyzed empirical and theoretical data from scientific publications over the last five years. The findings indicate that this regulation has significantly improved operational efficiency and patient satisfaction in healthcare facilities. Several studies highlight improvements in patient identification protocols, risk management, and compliance with healthcare service standards. However, there are challenges, such as gaps in technology infrastructure and training for implementing electronic medical records (EMR), uneven distribution of specialist doctors, and deficiencies in the framework for public-private partnerships.